(untitled) (Altre Modernità, 2022)
In the wake of the so-called ’second wave’ of feminism, which is already told linguistically in terms of epidemiological diffusion, there are two stories by Dino Buzzati and Primo Levi, in which female emancipation assumes the fantastic features of a prodigious and dangerously contagious disease. Placed at the end of the ’unfortunate’ collection Restless Nights, “The Count’s Wife” is one of Buzzati’s rare forays into the feminine, in which he shows his understanding and sarcastic intolerance towards the marriage prototypes of contemporary society. The wings that sprout on the back of the young and beautiful wife of Count Giorgio Venanzi, terrified by the idea of a scandal, allow her to escape, albeit momentarily, from the daily routine of married life, which she espoused at a very young age. The miracle of flight is also mysteriously granted, in very similar circumstances, to Isabella, the protagonist of Levi’s “The Great Mutation”, who is scrupulously examined by a doctor that finds her to be highly contagious. Having overcome her initial shame, the young woman fully savours the advantages of the freedom that is mysteriously bestowed upon her and finally comes out to the world. The event is experienced with mortification and shame by her father who, having been infected along with the doctor and some of her classmates, ends up opting for an amputation.